Silas House : Exploring an Appalachian Writer's Work - Shurbutt, Sylvia Bailey (Book collections on Project MUSE., 2021)
"Bestselling author, music journalist, playwright, and activist Silas House has focused nearly all of his work on Appalachia, its people, and its cultures. His acclaimed and diverse body of work includes the novels Clay's Quilt, A Parchment of Leaves, The Coal Tattoo, Eli the Good, and Southernmost. Pulitzer Prize-winning historian Studs Terkel praised his book Something's Rising: Appalachians Fighting Mountaintop Removal, coauthored with Jason Kyle Howard, as "oral history at its best." Well known for its lyrical style, diverse and sympathetic characters, and political engagement, House's work is overdue for deeper critical study. In this groundbreaking book, editor Sylvia Shurbutt brings together established and rising scholars to discuss the author and his writings through a critical lens. Various chapters address different aspects of House's fiction and nonfiction, including the ways in which he deconstructs regional stereotypes, how he explores issues of diversity, and how House-a musician himself-infuses his writing with music and musical motif's. The contributors also consider his environmental activism and his approach to LGBTQ issues. The collection concludes with a chapter by celebrated poet Maurice Manning exploring the lyricism that distinguishes House's work and a foreword by Denise Giardina. Featuring an interview with the author that further illuminates his philosophy and art, this timely volume offers an important critical appraisal of Silas House's oeuvre to date and illustrates why he is one of the most engaging voices in Appalachian and American literature today"--